Enhancing Brand Awareness through Content Marketing Strategy Analysis in the Digital Landscape - Harlen Silalahi; Saut Guna (Journal on Economics, Management and Business Technology, 2024)
This research explores content marketing strategies aimed at increasing brand awareness in the digital landscape. By analyzing existing literature, theoretical frameworks, and empirical studies, the study identifies key components of effective content marketing strategies and their impact on brand awareness. The research employs a mixed-methods approach, combining quantitative surveys with qualitative case studies, to provide a comprehensive understanding of content marketing practices and their effectiveness. Findings reveal the importance of clear objectives, audience research, diversified content types, strategic distribution, search engine optimization, engagement, measurement, and continuous improvement in content marketing strategies. Despite the potential benefits of content marketing, challenges such as content overload, audience fragmentation, measurement difficulties, and resource constraints persist. However, by integrating research findings into their strategies, businesses can overcome these challenges and maximize the impact of their content marketing efforts.